1974
DOI: 10.2307/3896435
|View full text |Cite
|
Sign up to set email alerts
|

Root Dynamics of a Shortgrass Ecosystem

Abstract: OF DISSERTATION ROOT DYNAMICS OF A SHOR TGRASS ECOSYSTEMSeasonal dynamics of roots of a shortgrass system were deter mined by samples collected at two week intervals for two growing seasons (1969)(1970) with a fall and winter sampling period in between.Soil cores were taken to a depth of either 10 cm or 80 cm; the deep cores were used to determine the entire profile distributions of roots.The cores were washed free of soil particles and then the root mass was dried, weighed, ashed and reweighed. All values wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 34 publications
3
16
0
1
Order By: Relevance
“…These relative differences in root yield at the community level also agree reasonably well with the differences in root growth of both species recorded under the controlled conditions. The high proportion of root mass of both species found in the surface zone of the soil profile in this study has been recorded in other range grasslands (Weaver & Albertson 1943;Bartos& Sims 1974).…”
Section: Discussionsupporting
confidence: 74%
“…These relative differences in root yield at the community level also agree reasonably well with the differences in root growth of both species recorded under the controlled conditions. The high proportion of root mass of both species found in the surface zone of the soil profile in this study has been recorded in other range grasslands (Weaver & Albertson 1943;Bartos& Sims 1974).…”
Section: Discussionsupporting
confidence: 74%
“…Belowground NPP was estimated in 1995 with the use of 12.5 cm diameter soil cores. In May and October, 10 samples per pasture were taken, to a depth of 20 cm, and were processed using the method of Bartos and Sims (1974). Root material was oven‐dried for 12 h at 60°C and was ashed for 8 h at 480°C (Goering and Van Soest 1970).…”
Section: Methodsmentioning
confidence: 99%
“…The soil temperatures differed less between the rangeland conditions with depth. To the contrary, in the North American prairies was found that root growth is associated with increases in soil temperature (in areas with winter snow) and water in spring and summer (Dahlman and Kucera, 1965;Bartos and Sims, 1974). Unfortunately little is known about the way in which root systems integrate the effects of wide ranges of temperature between different zones (Drew, 1979;Distel and Fernandez, 1988).…”
Section: Soil Temperaturementioning
confidence: 99%